Kinetics of the photolysis and OH reaction of 4-hydroxy-4-methyl-2-pentanone: Atmospheric implications. (February 2017) - Aslan, L.; Laversin, H.; Coddeville, P.; Fittschen, C.; Roth, E.; Tomas, A.; Chakir, A.
Abstract: This study provides the first kinetic and mechanistic study of the photolysis of 4-hydroxy-4-methyl-2-pentanone (4H4M2P) and the determination of the temperature dependence of the relative rate coefficient for the reaction of OH radicals with 4H4M2P. The UV absorption spectrum of 4H4M2P was determined in the spectral range 200–360 nm. The photolysis frequency of this compound in the atmosphere was evaluated relative to actinometers and found to be J 4 H 4 M 2 P a t m = 4.2 × 10 − 3 h − 1, corresponding to a lifetime of about 10 days. Using 4H4M2P cross section measurements, an atmospheric effective quantum yield of 0.15 was calculated. The main primary photolysis products were acetone (121 ± 4) % and formaldehyde (20 ± 1) %. A low methanol yield of (3.0 ± 0.3) % was also determined. These results enabled us to propose a mechanistic scheme for the photolysis. Rate coefficients for the reaction of 4H4M2P with OH radicals were determined over the temperature range 298–354 K and the following Arrhenius expression was obtained: kOH+4M4H2P  = (1.12 ± 0.40) × 10 −12 exp(461.5 ± 60/T) cm 3  molecule −1  s −1 . The lifetimes of 4H4M2P due to reaction with OH radicals has been estimated to ∼2.5 days and indicates that the gas-phase reaction with the OH could be the main loss process for this compound. Graphical abstract: Highlights: This work provides the kinetic of the photolysis and OH reaction of 4H4M2P. Slight negative temperature dependence in the OH + 4H4M2P reaction kinetics. Results are compared to those found in literature. The tropospheric lifetimes of this compound is estimated.